2020
DOI: 10.1101/2020.09.02.274969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triplet-Triplet Annihilation PLGA-Nanoparticles for Cancer Bioimaging

Abstract: Triplet-triplet annihilation upconversion (TTA-UC) nanoparticles (NPs) have emerged as imaging probes and therapeutic probes in recent years due to their excellent optical properties. In contrast to lanthanide ions-doped inorganic materials, highly efficient TTA-UC can be generated by low excitation power density, which makes it suitable for clinical applications. In the present study, we used biodegradable poly(lactic-co-glycolic acid) (PLGA)-NPs as delivery vehicle for TTA-UC based on the heavy metal porphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In this study, we applied the BBD, since this method is widely used to optimize the NPs formulation processes and demonstrated high prediction accuracy for NPs characteristics [45,91]. To obtain MePloaded NPs, we used nanoprecipitation and single emulsion-solvent evaporation methods, since they are commonly used for MeP encapsulation into a polymer matrix [102][103][104]. During the optimization process, we found that each MeP was characterized by a different influence of factors (PLGA mass, PVA concentration, O/W phase ratio) on PS and LC.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%
“…In this study, we applied the BBD, since this method is widely used to optimize the NPs formulation processes and demonstrated high prediction accuracy for NPs characteristics [45,91]. To obtain MePloaded NPs, we used nanoprecipitation and single emulsion-solvent evaporation methods, since they are commonly used for MeP encapsulation into a polymer matrix [102][103][104]. During the optimization process, we found that each MeP was characterized by a different influence of factors (PLGA mass, PVA concentration, O/W phase ratio) on PS and LC.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%